2004
DOI: 10.1248/bpb.27.189
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Effect of Peptides from Royal Jelly in Spontaneously Hypertensive Rats

Abstract: We have shown that Protease N treated Royal Jelly (ProRJ) and peptides from ProRJ (Ile-Tyr (IY), Val-Tyr (VY), Ile-Val-Tyr (IVY)) inhibited angiotensin I-converting enzyme (ACE) activity and they have an antihypertensive effect in repeated oral administration for 28 d on spontaneously hypertensive rats (SHR). We investigated the contributive ratio of these peptides in ProRJ for antihypertensive effect in single oral administration on SHR. In single oral administration of each peptide and peptides mixture (MIX;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(97 citation statements)
references
References 12 publications
2
94
0
1
Order By: Relevance
“…Commercial RJ is obtained by harvesting the brood food from the queen cell in the 3rd day of larval development (ISO 12824:2016). (Fujii et al, 1990;Kohno et al, 2004), immunoregulatory (Okamoto et al, 2003;Vucevic et al, 2007), insulin-like (Dixit and Patel, 1964;Kramer et al, 1982), estrogen signaling mediating (Moutsatsou et al, 2010), antiaging (Inoue et al, 2003), reducing cholesterol levels (Kashima et al, 2014), vasodilation (Tokunaga et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Commercial RJ is obtained by harvesting the brood food from the queen cell in the 3rd day of larval development (ISO 12824:2016). (Fujii et al, 1990;Kohno et al, 2004), immunoregulatory (Okamoto et al, 2003;Vucevic et al, 2007), insulin-like (Dixit and Patel, 1964;Kramer et al, 1982), estrogen signaling mediating (Moutsatsou et al, 2010), antiaging (Inoue et al, 2003), reducing cholesterol levels (Kashima et al, 2014), vasodilation (Tokunaga et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated a wide range of health benefits to humans and model organisms, including vasodilative and hypotensive activities (Tokunaga et al, 2004), antitumor (Tamura et al, 1987), anti-inflammatory (Fujii et al, 1990;Kohno et al, 2004), antibacterial and disinfectant properties (Fujiwara et al, 1990;Shen et al, 2010a), antifatigue activity (Kamakura et al, 2001a), and increasing the average lifespan in mice (Inoue et al, 2003) and nematodes (Honda et al, 2011). Because of its great potential benefits to human health, RJ is widely used as a key component in many commercial products including medicine, dietary supplements, and cosmetics (Kamakura et al, 2001c).…”
Section: Introductionmentioning
confidence: 99%
“…Hypotensive effects of ACE-inhibitory peptides from royal jelly (Tokunaga et al, 2004), egg white hydrolyzate (Miguel et al, 2005), and jellyfish (Morinaga et al, 2010) were observed in SHR following a single oral administration. The 2 peptides isolated from A. americana tuber hydrolyzate in the present study showed hypotensive effects in SHR equal to or greater than those isolated previously.…”
Section: Fig 1 Hplc Chromatogram Of Peptides In the S2 Fraction Shmentioning
confidence: 98%